Development of a conceptual framework to improve sexual wellbeing communication in routine prostate cancer care. Issue 6 (June 2020) - McCaughan, Eilís; Parahoo, Kader; Flannagan, Carrie; Maguire, Roma; Connaghan, John; Steele, Mary; Thompson, Samantha; Jain, Suneil; Kirby, Mike; Brady, Nuala; O'Connor, Seán R
Highlights: A conceptual framework for sexual wellbeing communication in routine prostate cancer care was developed. This was based on data from evidence reviews, semi-structured interviews and testing using 'think-aloud' methods. The framework consisted of 'Engagement' (E), 'Assessment' (A), 'Support' (S) and 'Sign-posting' (Si) sections. The EASSi framework can facilitate and structure conversations, ensuring fundamental, individualised support is provided. Abstract: Objective: To systematically develop a framework to improve sexual wellbeing communication in routine prostate cancer care. Methods: The Theoretical Domains Framework was used to guide a multi-phase process used to identify components of the framework based on evidence reviews, semi-structured interviews and stakeholder workshops. 'Think-aloud' testing was used to explore usability, potential barriers and other factors relevant to implementation. Results: A conceptual communication framework consisting of 'Engagement' (E), 'Assessment' (A), information and 'Support' (S) and 'Sign-posting' (Si) sections was developed. The framework emphasises routine engagement to normalise sexual concerns, brief, non-sensitive assessment, personalised advice based on treatment type and relationship status, and a mechanism for referral to additional support or self-management resources in the form of a patient and partner handout. Usability testing identified strategies to promote implementation. Conclusions: The proposed framework is appropriate for use in routine practice and appears to be acceptable to patients, partners and healthcare professionals. Its use may help address gaps in sexual wellbeing support for men and partners living with prostate cancer. Further work will be conducted evaluating an online engagement tool, modelled on the framework. Practice Implications: The EASSi framework can facilitate and structure sexual wellbeing conversations and ensure fundamental but individualised support is provided routinely in prostate cancer care.